Escalas para avaliação do risco de suicídio em adolescentes : revisão sistemática - Camargo, Maria Ida Ferreira Pires de (2024)
Adolescence can be a time of considerable physical, psychological, cognitive and sociocultural changes. Studies and global estimates indicate that suicide represents the third cause of death. In this sense, it becomes evident that the study of suicide risk can contribute important information to understanding suicidal behavior, especially in adolescence. Given this context, the objective of this research was to analyze, identifying and comparing, suicide risk assessment scales in adolescents. This was a systematic review, structured according to the guidelines of the Preferred Reporting Items for Systematic Reviews and Meta-Analysis – PRISMA (2020) checklist. The research question constructed using the PECO strategy was: What are the types and validity criteria of suicide risk scales in adolescents? The indexers used in the article searches were: Pubmed, Cochrane and Web of science, as well as the Brazilian Digital Library of Theses and Dissertations – BDTD as gray literature. The design comprised any type of quantitative study, published in the last five years (from 2018 to 2022) and without language restrictions. 15 articles were selected for the review, containing 14 types of scales with studies bringing the main validity and reliability criteria and 4 scales entirely aimed at the risk of suicide in adolescents, namely: The Adolescent Suicidal Behavior Assessment Scale (SENTIA) ( Adriana Díez-Gómez et al., 2020), Kutcher Adolescent Depression Scale (Zhou Huiming et al., 2015), Suicidal Ideation Questionnaire–Junior (SIQ-JR) (Reynolds, 1987), and Reasons to Live For Inventory Adolescents (RFL) (Osman et al., 1998). The identification and comparison of scales, considering their validity and reliability criteria, contribute to the development of instruments that directly serve adolescents known to be vulnerable to the phenomenon addressed in this study.